INTRODUCTION. FIRST CONFERENCE OF THE ICHU, APRIL 1994

(untitled) (Les Presses de l’Université de Montréal, 1994)
This document describes the theoretical and practical context for the essays (published as 302-310) that were distributed to participants of the first meeting of the International Conference for Humanistic Discourse.